Relationships between parental socialization goals, positive parenting, self-regulation and social competence among Malaysian preadolescents - Gan, Su Wan (2017)
Building social competence is a key developmental task for preadolescents. Parents as the primary socializing agents are responsible in promoting social competence among their preadolescent children. Grounded by Contextual Model of Parenting Style (Darling & Steinberg, 1993) and Self-Determination Theory (SDT) (Deci & Ryan, 1985; Ryan & Deci, 2000), this study aimed to examine the relationships between parental socialization goals, positive parenting, self-regulation and social competence among Malaysian preadolescents. This study applies descriptive correlational design with a survey method. A total of 711 preadolescents aged 10 to 12 years and their parents were recruited as respondents by using multistage proportionate-to-size sampling technique. Established instruments which are Socialization Goals Questionnaire (Li et al., 2010), Parental Beliefs Scale (Padmawidjaja & Chao, 2010), Parents as Social Context Questionnaire (Skinner et al., 2005), Questionnaire of Self-regulation (Novak & Clayton, 2001), and Individual Protective Factors Index (Springer & Phillips, 1997) were used to measure the main variables in this study. Self-administered questionnaire was used for data collection. AMOS software was applied to investigate hypothesized model that examined the relationships between parental socialization goals (i.e., collectivism socialization and child-centered goals), positive parenting, self-regulation and social competence. As hypothesized, parental socialization goals worked as causal factors of positive parenting. The results of the study also revealed that positive parenting contributed to higher level of self-regulation; however, it failed to predict social competence. Findings of the study also found that self-regulation had a direct contribution to higher level of social competence among preadolescents. The mediating role of self-regulation on the relationship between positive parenting and social competence was confirmed by bootstrapping procedure. Within the mediation model, self-regulation fully mediated the relationship between positive parenting and social competence. The results revealed that parents with positive parenting can help to develop higher level of self-regulation among preadolescents; thus, self-regulated preadolescents reported to have higher level of social competence. Multigroup analysis was implemented to test the moderating effect of ethnic groups (i.e., Malay, Chinese, and Indian) on the path of parental socialization goals and positive parenting within the model. The results of Chi-square difference test reported that there were no significant differences for the paths from collectivism socialization and child-centered goals to positive parenting among Malay, Chinese and Indian parents. The results indicated that both collectivism socialization and child-centered goals lead to performance of positive parenting among Malay, Chinese and Indian parents. This study concluded that parents with collectivism socialization and child-centered goals are more likely to perform positive parenting, which in turn contributed to social competence through the promotion of self-regulation. The findings can enhance understanding on parental socialization goals and its predictive role in positive parenting among Malaysian parents. The findings can also be applied for parents from similar ethnic groups in other countries. Parents should strengthen their positive parenting in order to foster self-regulated and socially competent preadolescents.